Соціальна комунікація в комп`ютерній робототехнічній грі - Лугова, Тетяна; Блажко, Олександр; Рященко, Оксана (Видавництво Львівської політехніки, 2019)
The paper describes a computer game model with Arduino microcontroller sensors in the form of a nondeterministic finite state machine states and connections of virtual and real objects.
Keywords: комп’ютерна гра; Arduino; робототехніка; Education Robotics; автоматна модель